Harmonisasi Hukum Perkawinan Adat Bali dengan Hukum Positif Indonesia - Adityadarma Bagus Priasmoro Suryono Putro; Uwais Deffa I. Qorni; Hanis Aristya Hermawan; RR. Alysia Gita Purwasaputri; Aditama Nur Ilham Pramulia (Jurnal Hukum Lex Generalis, 2020)
Adat law is a set of written and unwritten norms that have lived in communities since historical period. In some regions in Indonesia that are still thick with customs and culture, customary practices are often carried out which often results in inconsistent with positive Indonesian Law. The practice of Ngarorod Marriage is a tradition of the Balinese people could raise questions with Indonesian legal regulations, especially Law No. 1 of 1974 concerning Marriage. The kinship position and the difference of the female caste is higher than the men being, is one of the causes of the Ngerorod custom.